Pharmacokinetics of Lidocaine and Its Metabolites Following Vaginal Administration of Lidocaine Gel to Healthy Female Subjects. Issue 1 (4th August 2016) - Martell, Bridget; Kushner, Harvey; Richardson, Elaine; Mize, Amy; Mayer, Philip
Abstract: Lidocaine vaginal bioadhesive gel is being developed as a local anesthetic for use in minimally invasive outpatient gynecological procedures and was investigated in single‐dose and multiple‐dose studies in healthy young adult women. Lidocaine doses of 2.5%, 5%, and 10% (w/w) were administered, and parent drug and metabolites monoethylglycinexylidide and glycinexylidide were measured in plasma. Lidocaine was absorbed through vaginal tissue and into the systemic circulation in a dose‐proportional manner, and there was little systemic accumulation. Plasma concentrations were 10‐ to 20‐fold lower than concentrations obtained after administration of intravenous lidocaine used to treat arrhythmic activity, thus demonstrating a wide safety margin for a vaginal lidocaine product.